Application of Remote Sensing for Delineating Area of Interest (AoI) in Parakasak Geothermal Potential Area, Banten - Elfinurfadri, Fahrian; Novitasari, Indah; Siagian, Haris Munandar; Novranza, Kms (Proceedings of the International Conference on Green Technology, 2017)
Remote sensing can contribute to icrease survey’s effectiveness and efficiencies in geothermal exploration. By using remote sensing, geophisical survey in geothermal exploration can be focused on Area of interest (AoI). Parakasak is a geothermal potential area in Banten, Java with appearance several surface manifestations such as kaipohan, hot springs, warm springs and cold springs. This research uses free Landsat 8 OLI imagery that free downloaded from www.earthexplorer.usgs.gov . The landsat is processed with some software such as global mapper, ER mapper and surfer. Interpretation of remote sensing data for mapping linements and geological structure is conducted by manual observation. The result finds geological structure that identified as rim caldera and appearance of several surface manifestations is correlated to the lineaments. The result also shows that the main direction of the lineaments developed in Parakasak geothermal prospect area is Northwest-Southeast. Area of Interest (AoI) as recommendation geophisical survey of Parakasak geothermal protential area is located on northern area of the Mt. Parakasak peak.